Gene expression data support the hypothesis that Isoetes rootlets are true roots and not modified leaves. - Hetherington, AJ; Emms, DM; Kelly, SB; Dolan, L (Springer Nature, 2020)
Rhizomorphic lycopsids are the land plant group that includes the first giant trees to grow on Earth and extant species in the genus Isoetes. Two mutually exclusive hypotheses account for the evolution of terminal rooting axes called rootlets among the rhizomorphic lycopsids. One hypothesis states that rootlets are true roots, like roots in other lycopsids. The other states that rootlets are modified leaves. Here we test predictions of each hypothesis by investigating gene expression in the leaves and rootlets of Isoetes echinospora. We assembled the de novo transcriptome of axenically cultured I. echinospora. Gene expression signatures of I. echinospora rootlets and leaves were different. Furthermore, gene expression signatures of I. echinospora rootlets were similar to gene expression signatures of true roots of Selaginella moellendorffii and Arabidopsis thaliana. RSL genes which positively regulate cell differentiation in roots were either exclusively or preferentially expressed in the I. echinospora rootlets, S. moellendorffii roots and A. thaliana roots compared to the leaves of each respective species. Taken together, gene expression data from the de-novo transcriptome of I. echinospora are consistent with the hypothesis that Isoetes rootlets are true roots and not modified leaves.